Synthesis and Characterization of Pollen Extract Mediated Gold Nanostructures - BAKAR, Fatma; SÖNMEZ, Hamide; EVECEN, Senanur; TURAN, Buse; DEMİR, Mehmet; GÜMÜŞ, Abdurrahman; ÇETER, Talip; YAZGAN, İdris (Bingol Universitesi, 2020)
There is an increasing demand in the synthesis of shape and size-controlled gold nanostructures (Au NSs) with greener methods. Therefore, we aimed to synthesize differently shaped and sized Au NSs using a greener technique under ambient conditions. In this study, we utilized pollen extracts of Corylus avellana, Juniperus oxycedrus and Pinus nigra species (collected from Kastamonu region of Turkey) for the synthesis. The extraction was performed in water in order to recover water soluble content from the pollen grains. The extracts were used to stabilize, and shape/size direct the HEPES (4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid) buffer synthesized Au NSs. UV-vis, powder X-ray diffraction (PXRD), scanning electron microscopy (SEM) characterizations proved synthesis of spherical, anisotropic and large Au NSs with this benign approach. The obtained Au NSs were possible to separate small and large Au NSs through centrifugation. Chemistry of pollen extracts played key role on morphology and stability of the Au NSs. The findings, for the first time, is revealing the synthesis of large Au nanorod bundles (>300 nm) along with hexagonal and spherical Au NSs under ambient conditions using pollen grain extracts, whose maturation took 24h.
Keywords: Engineering; gold nanostructure; gold nanorod; pollen grain extract; Mühendislik